Below the waterline: cryptic diversity of aquatic pipid frogs (Pipa carvalhoi) unveiled through an integrative taxonomy approach. Issue 8 (8th August 2020) - Lima, Luana Rodrigues; Bruschi, Daniel Pacheco; Do Nascimento, Filipe Augusto Cavalcanti; Scherrer De Araújo, Paulo Victor; Costa, Leonora Pires; Thomé, Maria Tereza Chiarioni; Garda, Adrian Antonio; Zattera, Michelle Louise; Mott, Tamí
Abstract : An integrative taxonomy approach is used to study the diversity of the Brazilian aquatic pipid frog Pipa carvalhoi, evaluating whether within this nominal species two or more lineages are evolving independently. To test these competing scenarios, we analysed morphological (tadpoles and adults), molecular (16S rRNA) and karyological data for up to 109 specimens to check for corroborating patterns among characters evolving under different selective pressures. Three well-supported haplogroups were recovered and their distributions match major hydrographic basins: clade I occurs in the North-eastern Atlantic river basin, clade II in the São Francisco and East Atlantic river basins, and clade III in the South-eastern Atlantic river basin. A bPTP species delimitation analysis recovered three candidate species, congruent with the clades recovered in the molecular phylogenetics. Genetic distances among the three clades of P. carvalhoi were higher than the expected value for interspecific divergence in the genus recovered using LocalMinima. Despite the lack of differences with conventional cytogenetic markers, in situ fluorescence hybridization of microsatellite repeats shows clade-specific differences in the accumulation and distribution of the microsatellite motif (GACA)4 among karyotypes. The morphology of adults from different localities was similar, whereas the morphometric characters of tadpoles revealed morphological clusters that partially match the genetic structure. Our results show a strong genetic structure that indicates that P. carvalhoi is actually three cryptic species, apparently related to hydrographic basins. Additional data on nuclear molecular markers, fine-scale geographic distribution, and possibly other sources (acoustic and internal morphology) are needed to further test and potentially describe these lineages as distinct species.